Strategi Komunikasi Bisnis Efektif Mahasiswa Prodi S1 Manajemen melalui Pembelajaran Kolaboratif - Afandi Rachman; Moh. Tahang; Budi Prajogo (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
This study aims to analyze the effectiveness of collaborative learning in enhancing business communication skills among management students. The research involved 60 undergraduate management students at STIE Ganesha, enrolled in Business Introduction and Business English courses. Conducted over four months (February–May 2025), the study employed a mixed-method approach, including quantitative and qualitative data collection. Data were gathered through questionnaires, interviews, and classroom observations. Descriptive statistics, regression analysis, and thematic coding were used to analyze the data. The results show that 78% of students gained greater confidence in presenting ideas, 65% improved their use of business terminology, and 70% became more active listeners. Regression analysis confirmed a significant influence of collaborative learning on communication skills (p < 0.05). Qualitative findings emphasized the importance of lecturers’ facilitation in managing group dynamics and addressing dominance issues among students. The study suggests that the integration of collaborative learning methods into the management curriculum is crucial for enhancing students' soft skills, preparing them for future professional challenges. Additionally, it advocates for the development of structured collaborative activities to promote effective teamwork, active engagement, and better communication outcomes in academic settings, ultimately contributing to students' overall personal and professional growth.